National health insurance membership among urban poor societies in Indonesia in 2019: Are they protected? - Agung Dwi Laksono; Rukmini Rukmini; Tumaji Tumaji; Mara Ipa; Ratna Dwi Wulandari (Economies, 2022)
Urban poor societies were a vulnerable group. Once they are sick, they fall deeper into poverty. National Health Insurance (NHI) is a way the government initiated to overcome this situation. We analyzed the factor related to NHI membership among urban poor societies. The study population included everyone living in urban poor societies. The study examined a sample of 3455 participants, and examined five characteristics: NHI, age, gender, education, employment, and marital status. In the final step, the research used binary logistic regression. The results show that all age groups are more likely than those over 64 to be a member of NHI among urban poor societies in Indonesia. Males have a 1.039 times higher chance than females to be a member of NHI. All education levels have less possibility than no education to be a member of NHI among urban poor societies in Indonesia. Employees have an opportunity of 1.097 times higher than the unemployed to be a member of NHI. All marital statuses have more possibility than those who are divorced or widowed to be a member of NHI among urban poor societies in Indonesia. The study results strengthen previous studies with a similar topic. We concluded that the NHI adequately protects urban poor societies. However, the government still has homework to pay attention to the remaining 28.3% of urban poor societies that the NHI has not covered.
Keywords: 330; big data; health insurance; health policy; national health insurance; population survey; public health; urban poor society